Currents and topography drive assemblage distribution on an active hydrothermal edifice. (August 2020) - Girard, Fanny; Sarrazin, Jozée; Arnaubec, Aurélien; Cannat, Mathilde; Sarradin, Pierre-Marie; Wheeler, Benjamin; Matabos, Marjolaine
Highlights: Assemblage distribution and hydrothermal activity vary between sides of the edifice. Distance from fluid exits predicts the distribution of most assemblages. Hydrothermal plumes can affect assemblages meters away from smokers. Exposure to plumes brought by currents fully explains microbial mat distribution. Significant role of currents and topography in shaping vent communities. Abstract: The deep sea is characterized by a wide range of landscapes, including complex features where topography and currents interact to form highly heterogeneous habitats. In addition to a complex topography, hydrothermal vent environments are characterized by strong environmental gradients that structure the spatial distribution of biological communities. The role of vent fluid temperature and chemical composition on species distribution is now well understood, but investigations on the effects of the complex sulfide edifice topography are scarce. Here, we used a novel approach combining 3D photogrammetric reconstruction, in situ environmental measurements and modeling to characterize assemblage distribution on the active edifice Eiffel Tower (Lucky Strike, Mid-Atlantic Ridge). Through the analysis of a high-resolution 3D model of the edifice, we show that assemblage distribution along with hydrothermal activity vary with their position on the edifice. Although physical terrain variables had a minor effect on assemblage distribution, the distance from fluid exits explained the distribution of most assemblages. However, these particular variables did not significantly explain the distribution of medium-sized Bathymodiolus azoricus mussels, the dominant assemblage on the edifice. Similarly, proximity to fluid exits only partially accounted for the distribution of microbial mats throughout the edifice. By modeling the current-driven dispersion of hydrothermal plumes around the edifice, we demonstrated that differences in mussel sizes may be due to differences in exposure time to currents bringing plume material. For the first time, we provide evidence that hydrothermal plumes can affect faunal assemblages meters away from fluid exits and that this relatively long-distance effect of vent plumes can fully account for microbial mat distribution throughout the edifice. Our findings extend the area of influence of hydrothermal plumes on vent communities considerably beyond previous estimations and suggest that the interactions between bottom currents, topography and smoker locations should be further investigated and considered as important structuring factors at vents. This novel approach, allowing to cover large areas of the seafloor, is particularly well suited for deep environments where topography and currents interact to form complex oceanographic patterns (e.g. canyons, seamounts). Its application to larger areas and various ecosystems can significantly enhance our understanding of benthic communities' distribution at large.